2020
DOI: 10.1007/s00259-020-05111-3
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the invisible—prevalence, characteristics, and radiomics feature–based detection of visually undetectable intraprostatic tumor lesions in 68GaPSMA-11 PET images of patients with primary prostate cancer

Abstract: Introduction Primary prostate cancer (PCa) can be visualized on prostate-specific membrane antigen positron emission tomography (PSMA-PET) with high accuracy. However, intraprostatic lesions may be missed by visual PSMA-PET interpretation. In this work, we quantified and characterized the intraprostatic lesions which have been missed by visual PSMA-PET image interpretation. In addition, we investigated whether PSMA-PET-derived radiomics features (RFs) could detect these lesions. Methodology This study consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 53 publications
1
55
0
1
Order By: Relevance
“…Recently, 68 Ga-PSMA PET/CT showed satisfactory results to aid decision-making by con rming or eliminating the further need for biopsies [12][13][14]. However, according to the literature, approximately 10% of primary PCa are negative on PSMA-PET (exhibit no or minimal uptake) despite high PSA levels [15][16][17][18][19], which may be due to small lesion size or lesion con guration [15]. In literature by Zamboglou et al [15], their result indicated that the incidence of invisible PCa lesions was not correlated with patients' basic clinical parameters or basic SUV parameters derived from gross tumor volume PET(GTV-PET), and 40% of invisible lesions were clinically signi cant (ISUP>1) PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 68 Ga-PSMA PET/CT showed satisfactory results to aid decision-making by con rming or eliminating the further need for biopsies [12][13][14]. However, according to the literature, approximately 10% of primary PCa are negative on PSMA-PET (exhibit no or minimal uptake) despite high PSA levels [15][16][17][18][19], which may be due to small lesion size or lesion con guration [15]. In literature by Zamboglou et al [15], their result indicated that the incidence of invisible PCa lesions was not correlated with patients' basic clinical parameters or basic SUV parameters derived from gross tumor volume PET(GTV-PET), and 40% of invisible lesions were clinically signi cant (ISUP>1) PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate-specific membrane antigen positron emission tomography (PSMA-PET) is another novel PCa visualization technology, which is characterized by high-precision visualization of primary PCa masses and provides superior accuracy at initial staging. At the same time, in a small-scale cohort, researchers reported the high accuracy of PSMA-PET-derived radiomics features for the diagnosis of visually unknown PCa (47). A newly reported study proposed a nomogram combining clinical information and PSMA-PET information.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some studies have shown higher accuracy for hybrid PET/MRI compared to mpMRI [ 67 , 194 , 195 , 196 ]. Additionally, the novel field of radiomics has recently been exploited in PCa [ 215 ] and is expected to increase the accuracy of interpretation and prediction of the stage and outcome. Noteworthy, invasive biopsy has a significant false-negative rate [ 82 ], which can be reduced by the guidance of imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Machine-learning models have been shown to correlate with human readers in detecting primary PCa [ 213 , 214 ]. They also have improved diagnostic accuracy [ 215 ]. Also, the analysis of radiomics features could discriminate lesions with Gleason score 7 and ≥8, as well as predict LN positivity with AUC of >0.84 [ 213 ].…”
Section: Radiomicsmentioning
confidence: 99%